The World Bank Group Beyond the Crisis - Zoellick, Robert B. (World Bank, Washington, DC, 2018)
Robert B. Zoellick, President of the World Bank, addressed the following issues: seeds of crisis; the changing context; responsible globalization; the current role of the World Bank Group; the role of the World Bank Group in a new post-crisis World; and the reform agenda. He pointed to four aspects of Group’s future role: development finance; delivering knowledge products; the global public goods agenda (such as climate change and communicable diseases); and unforeseen future crises. Reform efforts include: 1) improving development effectiveness with a focus on results, decentralization, gender, investment lending reform, and human resources; 2) promoting accountability and good governance, and 3) increasing cost efficiency. He noted the completion of recent enhancements to the voice and representation of developing and transition countries in the Bank Group. Bretton Woods is being overhauled before our eyes.